Experimental poisoning with Pascalia glauca in goats - Medina, Diego M.; Colque Caro, Luis Adrián; Micheloud, Juan Francisco (Ediciones INTA, 2023)
Pascalia glauca is one of the most important poisonous plants in Argentina. Although goats are known to be sus ceptible to P. glauca poisoning, reports about this species are scarce. This work aimed to characterize the exper imental intoxication in goats with P. glauca. 12 adult Saanen goats were divided into 4 groups based on the amount of the plant given. Groups 1 to 3 ingested 4g/kg, 6g/kg and 8g/kg of dry plant respectively. The fourth group was the control group and it was offered alfalfa hay only. The poisoned animals were inspected every two hours and blood samples were collected 6, 12, 24 and 48 hours after poisoning to measure the level of liver enzymes. Clinically, groups 2 and 3 showed anorexia, depression, recumbency, myoclonus, seizures and death between 9 and 24 hours after poisoning. Pathologic findings included centrilobular necrosis with and without hemorrhages. Both groups showed elevated serum aspartate aminotransferase activity between 6 and 24 hours after P. glauca ingestion. The control group and group 1 did not show clinical signs or hepatic enzyme elevation despite being controlled for 15 days after the poisoning. This work allowed us to collect further information about the clinical and pathological aspects of P. glauca poisoning in goats.